Distribution, sources and transport of HCHs and DDTs in the Yuquandong spring system from Zigui County, Hubei Province - Xiuwen YANG; Zhiying WEI; Jiapei YI; Wenxing LI; Yiming JING; Chaojie QIN; Junwu XIONG; Wei LIU; Hong ZHOU; Shihua QI; Wei CHEN (地质科技通报, 2024)
The special topography of karst areas allows organochlorine pesticides (OCPs) from the surface environment to easily infiltrate the underground environment, posing a threat to groundwater security. Methods In this study, a gas chromatography-electron capture detector (GC-ECD) was used to detect two typical OCPs, namely, HCHs and DDTs, in the Yuquandong spring system in Zigui, Hubei. Objective This study investigated spatial and temporal distribution characteristics, sources and transport of HCHs and DDTs. Results The results showed that the mass concentrations of HCHs in the water ranged from 0.09 to 5.17 ng/L, and the mass fractions of HCHs in the soils and spring sedimentsranged from 0.36 to 3.67, 0.11 to 2.53 ng/g, respectively, mass concentrations of DDTs in the water ranged from 0.13 to 7.16 ng/L, and the mass fractions of DDTs in the soils and spring sedimentsranged from 0.22 to 19.13, 0.73 to 11.53 ng/g, indicating that the pollution was dominated by DDTs. The highest mass concentrations of HCHs and DDTs in water were observed in winter; the highest mass fractions of HCHs and DDTs in the soils were observed in summer and winter, respectively; and the mass fractions of HCHs and DDTs in the spring sediments peaked in summer and spring, respectively. Characteristic ratios showed that HCHs in water, soils and spring sediments mainly originated from lindane usage, DDTs in water mainly originated from historical residues, and DDTs in the soils and spring sediments mainly originated from recent usage. Correlation analysis indicated that HCHs and DDTs could be transported from the surface water and the soils in the recharge area to the spring water and spring sediments in the discharge area, respectively. The rapid transport of HCHs and DDTs across multiple media confirmed groundwater vulnerability in karst areas. Conclusion The study can provide a reference for the protection of karst groundwater resources and the environment.